Performing Bürgerlichkeit : the German bourgeoisie and contemporary theatre - Galt, Anna (Trinity College (Dublin, Ireland). Department of Germanic Studies, 2012)
This dissertation will investigate Bürgertum and Bürgerlichkeit and their relevance to the work of three contemporary German theatre directors; Michael Thalheimer, Thomas Ostermeier and René Pollesch. While the concept of class may have fallen out of favour in recent years, Bürgerlichkeit remains an important concept with regard to German culture, specifically in relation to theatre, not least because in Germany the theatre has been a bourgeois project from the start and a fundamental part of the bourgeois public sphere. In the last thirty years, there has been renewed academic interest in the social and cultural history of the Bürgertum, and its important role in the establishment of the value systems and cultural practices of modern culture.
Keywords: Languages, Literatures & Cultural Studies, Ph.D.; Ph.D. Trinity College Dublin.